2008
DOI: 10.1038/sj.sc.3102173
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of agonist–antagonist shoulder torque ratios in individuals with paraplegia: a new interpretative approach

Abstract: Study Design: Cross-sectional study. Objective: To evaluate isokinetic shoulder flexor-extensor (F/E) and abductor-adductor (Ab/Ad) torque ratios in individuals with paraplegia using a new interpretative approach. We proposed to study torque ratios according to joint angle sections (151 angle subgroups) over a selected range of motion. Setting: Pathokinesiology Laboratory, Montreal, Canada. Method: Sixteen individuals with complete motor paraplegia, without shoulder pain or impairment, were included in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…These results suggest that different sports [11] and surfaces where these sports are practiced [1] may result in different H/Q strength ratios, which may lead to specific imbalances necessary to the specific sports performance. Furthermore, the use of ratios based only on PT has been debated [38][39][40]. In a previous study from our laboratory [40], we demonstrated that there were differences in several angles when comparing shoulder rotators DCR calculated by PT and by a 10 • angle specific torque (AST) approach.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that different sports [11] and surfaces where these sports are practiced [1] may result in different H/Q strength ratios, which may lead to specific imbalances necessary to the specific sports performance. Furthermore, the use of ratios based only on PT has been debated [38][39][40]. In a previous study from our laboratory [40], we demonstrated that there were differences in several angles when comparing shoulder rotators DCR calculated by PT and by a 10 • angle specific torque (AST) approach.…”
Section: Discussionmentioning
confidence: 99%
“…This has also been shown to affect the interpretation of shoulder rotators unilateral strength imbalance [1], and many studies have opted to use an AST approach in order to gain more specific information of joint strength imbalances [1,3,4,[6][7][8]. We have previously demonstrated that shoulder IPT dynamic control ratios are significantly different than AST at several angles when calculated by 10° intervals over a 150° total ROM [1].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few studies have opted to use 5°, 10°, 15° or end of ROM angle specific torque (AST) intervals for a more accurate estimation of unilateral dynamic muscle balance of the knee or shoulder joints [1,3,4,[6][7][8][9]. Dehail et al [7] demonstrated there was a significant progressive decline of flexion/extension and abduction/adduction AST strength ratios as the shoulder progressed to flexion and abduction, respectively. Yildiz et al [4], found that although internal rotator eccentric strength of the preferred side was greater than the non-preferred side at the end of the ROM, only the internal rotator concentric strength was greater than the non-preferred side at the beginning of the ROM.…”
Section: Contextmentioning
confidence: 99%
See 2 more Smart Citations